IRON DEFICIENCY ANEMIA AND ANEMIA OF CHRONIC DISEASES: SOME ASPECTS OF THE PATHOGENESIS AND PROSPECTS OF DIFFERENTIAL DIAGNOSIS - Клочкова-Абельянц, Сатеник Аршавиловна; Суржикова, Галина Северьевна (Medicine in Kuzbass, 2019)
Objective – to evaluate the information content of modern methods for studying iron metabolism in the algorithm for the differential diagnosis of hypochromic anemias.Materials and methods. A total of 296 women aged 16 to 60 years with an anemic syndrome were examined, of which 103 women had IDA, and 193 had AHZ. The control group consisted of 79 healthy women.The study of hematological parameters of peripheral blood was performed by standard methods with the evaluation of morphofunctional parameters of erythrocytes. Soluble transferrin receptors (rTFR) and the content of hepcidin-25 were determined by an enzyme immunoassay method using test systems of JSC Vector-Best and Peninsula Laboratories, LLS.Main results. A significant increase in the rTFR level was found in patients with IDA compared with the group of individuals suffering from AHD (p = 0.000). An extremely low level of hepcidin was found in IDA – 0.46 ± 0.03 ng/ml, while in individuals with AHZ, the content of hepsidin was increased, averaged 45.05 and 39.33 ng/ml in AHZ against RA and in infectious and inflammatory processes, respectively, against 8.7 ± 0.31 ng/ml in healthy individuals (p = 0.000).Conclusions. Determining the amount of soluble transferrin receptors significantly increases the level of differential diagnosis of iron and iron deficiency and functional iron deficiency. The study of hepcidin levels is particularly valuable in cases of AHZ, where the assessment of iron reserves in terms of serum ferritin levels is not informative due to the paradoxical increase in ferritin levels associated with impaired iron utilization and storage mechanisms.
Keywords: iron deficiency anemia; chronic disease anemia; soluble transferrin receptors; hepcidin